Removal of used motor oil from water body using modified commercial activated carbon - S. M., Anisuzzaman; Sariah, Abang; D., Krishnaiah; Azlan, N.A. (Malaysian Institute of Chemistry, 2019)
In this study, modification of commercial activated carbon (AC) was carried out for adsorption of used motor oil (UMO) from wastewater. The modification process involved impregnation of phosphoric acid at ratio 1: 2 followed by 500oC for 2 h for carbonization. Characterization of modified activated carbon (MAC) was done by using scanning electron microscopy with energy dispersive X-ray spectrometry and Fourier transform infrared spectroscopy to study morphology and the structural change and to identify the surface functional group of MAC. Based on the results obtained from this study, the percentage yield of the MAC was 63 with a moisture content of 37, and pH was 2.37. The adsorption of UMO by MAC was investigated. The effect of contact time, temperature, and pH to the adsorption process was studied, where the results showed that MAC had higher percentage of adsorption compared to AC. The study of the reusability of MAC was also done for 30 min and three cycles. The result showed that MAC could be regenerated and reused. The study of adsorption equilibrium was done by using Langmuir and Freundlich isotherms. The adsorption of UMO proved to fit better to Freundlich isotherm compared to Langmuir isotherm with a value of 0.9174. The adsorption kinetic study was done using pseudo-first-order and pseudo-second-order models. The adsorption data showed a better fit to pseudo-first-order kinetic model with a value of 0.9239. Adsorption capacity was found to be 3.951 oil/g (MAC). Â© 2019 Malaysian Institute of Chemistry. All rights reserved.